The Iglesia ni Christo : a study of a new religious movement and exploration of culturally appropriate outreach methodologies - Harper, Anne Catherine (Philippines : Asia Graduate School of Theology, 2011)
This dissertation examines the Iglesia ni Cristo as a largely unreached New Religious Movement numbering approximately three million members. Originating in the Philippines, the religion has spread abroad with the Filipino diaspora. the study begins with a review of the literature on New Religious Movements, and then examines the historical context from which the Iglesia ni Cristo arose and the group's remarkable growth. the Filipino cultural context is examined through its values, and the impact of those values on the worldview of the Iglesia ni Cristo is discussed. The distinctive culture of the group is examined, and missiological literature discussing outreach methodologies to closely-knit cultures is discussed. Twelve case studies of those leaving the group to embrace evangelical Christianity are presented and analyzed. These show that conversion was a process lasting several years and that non-confrontational, relational methods were effective. Analysis of the case studies also shows that particular aspects of the gospel message are more appealing than others. This insight leads to the idea that gospel presentations to members of the Iglesia ni Cristo should not necessarily begin with the divinity of Christ, but with more attractive messages such as the divinity and empowering of the Holy Spirit, salvation and freedom from sin. The final chapter of the dissertation offers suggestions for contextual relational strategies for reaching out to members of this group with focus on conversion of entire family units and social networks.
Dissertation (D.Miss.)-Asia Graduate School of Theology
Includes bibliographical references (p.391-400) and index
Keywords: Iglesia ni Cristo (Church of Christ)